2019
DOI: 10.1002/nme.6069
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for stress and mixed control in Galerkin‐based FFT homogenization

Abstract: Summary A new algorithm is proposed to impose a macroscopic stress or mixed stress/deformation gradient history in the context of nonlinear Galerkin‐based fast Fourier transform homogenization. The method proposed is based on the definition of a modified projection operator in which the null frequencies enforce the type of control (stress or strain) for each component of either the macroscopic first Piola stress or the deformation gradient. The resulting problem is solved exactly as the original variational me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 13 publications
(44 reference statements)
0
38
0
Order By: Relevance
“…for E ∈ Sym(d) and u ∈ H 1 # (Y ; R d ). Kabel et al [187] and Lucarini and Segurado [188] showed that the problem (4.2) is equivalent to a Lippmann-Schwinger equation, which takes the form…”
Section: Mixed Boundary Conditionsmentioning
confidence: 99%
“…for E ∈ Sym(d) and u ∈ H 1 # (Y ; R d ). Kabel et al [187] and Lucarini and Segurado [188] showed that the problem (4.2) is equivalent to a Lippmann-Schwinger equation, which takes the form…”
Section: Mixed Boundary Conditionsmentioning
confidence: 99%
“…Journal Pre-proof average planar stretch is prescribed -see for example [37] for a comprehensive discussion of mixed boundary conditions). Above, • denotes spatial average.…”
Section: Implementation In the Periodic Settingmentioning
confidence: 99%
“…Classically, FFT methods are conceived to have the macroscopic strain as input and resolve the stress and mixed cases by iterative approaches. Very recently, the authors have proposed a method to include directly the prescribed terms of the macroscopic stress in the formulation [17] for the Galerkin-FFT approach. In this paper, we propose a similar approach for the DBFFT.…”
Section: Dbfft: Stress Controlmentioning
confidence: 99%